2020
DOI: 10.1186/s12887-020-02427-9
|View full text |Cite
|
Sign up to set email alerts
|

Value of Galectin-3 assay in children with heart failure secondary to congenital heart diseases: a prospective study

Abstract: Background Galectin-3 is a new biomarker, which plays an important role in tissue inflammation, cardiac remodeling, and fibrosis. It can be readily measured in the circulation to detect early heart failure (HF). This study aimed to assess the value of galectin-3 assay in early diagnosis of children with heart failure secondary to congenital heart disease (CHD) and correlate it with the patients’ outcome. Methods This prospective cohort study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Few studies have demonstrated the relationship of Gal-3 concentration and congenital heart disease in children. A recent study demonstrated that Gal-3 is a promising cardiac marker for early diagnosis of heart failure in children with congenital heart disease [37]. Moreover, a higher Gal-3 concentration in children with heart failure with normal or reduced ejection fraction compared with healthy controls was observed, whereas Gal-3 concentration was slightly higher in those with a normal ejection fraction [11].…”
Section: Resultsmentioning
confidence: 96%
“…Few studies have demonstrated the relationship of Gal-3 concentration and congenital heart disease in children. A recent study demonstrated that Gal-3 is a promising cardiac marker for early diagnosis of heart failure in children with congenital heart disease [37]. Moreover, a higher Gal-3 concentration in children with heart failure with normal or reduced ejection fraction compared with healthy controls was observed, whereas Gal-3 concentration was slightly higher in those with a normal ejection fraction [11].…”
Section: Resultsmentioning
confidence: 96%
“…In the studies conducted in pediatric patients with congenital heart diseases, galectin-3 plasma concentration was significantly higher in children presenting with heart failure signs and symptoms than in those without [ 19 , 20 , 21 , 22 ]. Moreover, galectin-3 levels correlated positively with the severity of circulatory system insufficiency expressed using the Ross Heart Failure Scale, and was lower in children treated with oral spironolactone than in those without [ 19 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the studies conducted in pediatric patients with congenital heart diseases, galectin-3 plasma concentration was significantly higher in children presenting with heart failure signs and symptoms than in those without [ 19 , 20 , 21 , 22 ]. Moreover, galectin-3 levels correlated positively with the severity of circulatory system insufficiency expressed using the Ross Heart Failure Scale, and was lower in children treated with oral spironolactone than in those without [ 19 , 21 ]. The evidence of correlation between galectin-3 plasma concentration and chosen echocardiographic parameters of left ventricular function, both systolic and diastolic, exists in the literature and was presented in the studies of Kotby et al and Saleh et al [ 19 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations